Local symptoms of Hashimoto’s thyroiditis: A systematic review - Yuan, Jiaojiao; Qi, Shuo; Zhang, Xufan; Lai, Hezheng; Li, Xinyi; Xiaoheng, Chen; Li, Zhe; Yao, Simiao; Ding, Zhiguo (Frontiers in Endocrinology, 2023)
Objective：Hashimoto’s thyroiditis (HT) is the most common type of thyroid disease and can cause many different manifestations. The local symptom of HT is an understudied area of research. Therefore, the purpose of this study was to investigate what are the local symptoms of HT and their prevalence. Methods: A systematic review was performed to find articles that discuss the local symptoms of HT in PubMed.A PubMed search was performed to find articles that discuss the local symptoms of HT. Relevant vocabulary terms and key terms included: autoimmune thyroid disease (AITD), hyperthyroidism, hypothyroidism, neck, throat, pharynx, airway, esophagus, breathe, swallow, globus, sleep apnea, symptoms, and quality of life. Two investigators independently screened the eligible studies. Results: A total of 54 articles fulfilled the inclusion criteria. Of these, 25 were clinical studies, 24 were case reports, and 5 were reviews. These clinical studies and case reports included a total of 2660 HT patients. There are 8 local symptoms related with HT: neck pain (0.02%~16%), voice changes (7%~30%), throat discomfort (20%~43.7%), shortness of breath (28%~50%), dysphagia (29%), goiter related symptoms (69.44%), sleep apnea, and generally defined compressive symptoms. Due to the use of different outcome measures amongst all the studies, a meta-analysis of the data could not be performed. Conclusion: Goiter symptoms, which is an item on the ThyPRO scales, is the most frequent local symptom in HT patients, and includes neck pain, voice changes, throat discomfort, and dysphagia. These local symptoms affecting the neck should be identified in clinic and included in early diagnosis and management of HT, as well as evaluated further to understand their relevance in the pathogenesis of HT.